2022
DOI: 10.1007/s43994-022-00001-w
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-aging trait of whey protein against brain damage of senile rats

Abstract: Aging mammalian results in impaired bio-functions and neurological disorders. The current study investigated whether whey protein (WP) syrup supplementation may improve age-related changes in diseased brain indicators like tau protein, β-amyloid and α-amylase. The study was carried out in conjunction with immunohistochemistry, histology, and flow cytometry of apoptosis. At the ages of 8 and 30 months, Wistar albino rats (Rattus novergicus) were divided into four groups (n = 8; G1; 8 months old rats; G2, 8 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…The present investigation proved that adding yeast extract to the medium resulted in the maximum phenol elimination efficiency and promoted the development of strain S3. The nature of yeast extract, easily obtainable as amino acids in a medium containing mineral salts, is needed for the phenol breakdown process by bacterial cells [ 60 , 61 ]. Mishra and Kumar [ 53 ] have shown that yeast extract is the optimum nitrogen source for growth and phenol decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…The present investigation proved that adding yeast extract to the medium resulted in the maximum phenol elimination efficiency and promoted the development of strain S3. The nature of yeast extract, easily obtainable as amino acids in a medium containing mineral salts, is needed for the phenol breakdown process by bacterial cells [ 60 , 61 ]. Mishra and Kumar [ 53 ] have shown that yeast extract is the optimum nitrogen source for growth and phenol decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…The compound N-(2-Allylcarbamoyl-4-chloro-phenyl)-3,4-dimethoxy-benzamide demonstrated the highest binding affinity, with a value of -6.7 kcal/mol, and can be further studied to develop possible medications against the mpox virus. In addition, nanomaterials and lead molecules derived from the natural products such as microbes and marine samples provide an opportunity to invent the drug molecules to treat the viral diseases [26] , [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Singleton et al [27] measured the total soluble phenolics of the DMSO fraction using the Folin-Ciocalteu reagent and gallic acid as the standard phenolic compound [28]. In separate test tubes, 40 µL of DMSO fraction and standard were transferred, and 200 µL of diluted Folin-Ciocalteu reagent was added.…”
Section: Chemical Composition Of Illicium Verum Extractmentioning
confidence: 99%